Penggunaan Cangkang Kemiri Sebagai Pengganti Sebagian Agregat Kasar Terhadap Kuat Tekan Dan Kuat Lentur Beton Dengan Zat Tambah Silica Fume - Marcelline, Aldo; Sariman, Syahrul; Yuniarto, Eka (Program Studi Teknik Sipil Universitas Bosowa, 2025)
The high demand for concrete in construction has increased the need for concrete materials, driving the mining of rocks as a primary component of concrete. Using simple technology that utilizes local resources, including waste as building materials, is essential for concrete technology development. Candlenut shells are a new potential material due to their hard texture. This study uses a design strength of 25 MPa for normal concrete, aiming to observe the effect of using candlenut shells as a partial coarse aggregate replacement with added Silica Fume on concrete's compressive and flexural strength. The mixing method involves replacing coarse aggregate with candlenut shells in 5%, 10%, and 15% proportions. Silica Fume is added at 20% of the cement weight for concrete without candlenut shells and with shell variations at 5%, 10%, and 15%. Results show that adding candlenut shells reduces compressive and flexural strength, but adding Silica Fume enhances both strengths. Notably, the 5% candlenut shell variation with 20% Silica Fume shows higher strength than normal concrete.